The Effects of Unrealistic Optimism on the Cognitive Intuition of Young Athletes in Selected Track and Field Events - Tayeh , Hind (Journal of Physical Education, 2025)
This research aimed to develop two measurement scales (i.e., one for the assessment of Unrealistic Optimism and another of Cognitive Intuition) and investigate the levels in young athletes, specifically from track and field. Furthermore, the study sought to examine whether there was a link between unrealistic optimism and cognitive intuition. The researcher tested the following the hypothesis: there is a significant relationship between both scales. A descriptive correlational approach was used, and the study sample included 198 young track and field athletes from clubs in Baghdad at season (2024 /2025). A purposeful sampling was used with 8 athletes as a pilot sample, 100 athletes for scale construction and 90 for main application sample. Having conducted the proper steps to develop these 2 scales, they were given to the main sample; and data were analyzed through SPSS. The results showed that both scales had strong validity and reliability, meeting the scientific standards for sports psychology tailored to young track and field athletes. Furthermore, the result also showed a strong positive correlation that high level of unrealistic optimism is related to higher level of cognitive intuition and vice versa. The study suggests that sports clubs should organize self-development programs, and also strengthen athletes’ cognitive skills. It is indicated the necessity of including a specialist in sports psychology when developing developmental and counseling programmed to reduce unrealistic optimism in young athletes as well as to conscious enhancing cognitive intuition.